CONTENIDOS AUDIOVISUALES EN SOCIAL MEDIA. ANÁLISIS COMPARATIVO DE FACEBOOK Y YOUTUBE - Dra. Carmen COSTA-SÁNCHEZ,Dr. Miguel TÚÑEZ-LÓPEZ (Fonseca, Journal of Communication, 2023)
Organizations that have entered into the new communicative paradigm (more participatory and dialogic) look for to approach to their publics through the spaces and channels where they interact and by means of a content strategy that help them to position and relate. The present work analyses the use of video/s in the two social networks with greater number of users in Spain: Facebook and Youtube